The Influence of the Manual Asymmetry on the Psycholinguistic Expression of the Students’ Sense of Language - Trihub, Galyna (Psychological Prospects Journal, 2015)
The article presents the results of the students’ sense of language empirical study considering the manual asymmetry. The sense of language is seen as a process and outcome intuitively sensory reflection of reality, based on the speech experience of a person and serves as a prerequisite for the formation of foreign language knowledge and foreign language competence in general. The sense of language serves as an intermediate between speech experience and language knowledge as follows:Speech experience → Sense of language →Language knowledge → Language competence. Speech experience is generated through effective verbal human behavior in different environmental situations. The molar unit of speech experience is the meaning of a word as an expression of various reality fragments content and personality’s attitude to them. The associative meaning of a word is appropriate for the language sense empirical study, as it allows to set the whole associative chain. Free associative experiment provides the first association to the offered words-stimuli (30 words). Reactions associations are grouped into two main types: central and peripherical. The speech specifics of left-handed first-year students served as a field of study. Empirically diagnostic speech study was carried out in two selections – right-handed and left-handed students (accordingly 60 and 15 persons), aged 17–18 years. Analysis of research demonstrates significant differences between the indices of logical central and peripherical reactions in two studied selections. The obtained results show that the left-handed students’ sense of language is formed worse in comparison with right-handed students.
Keywords: sense of language, speech experience, language knowledge, language competence, empirical study, association, stimuli, logical central reactions, logical peripherical reactions, meaning of a word